2007
DOI: 10.1063/1.2802564
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, stoichiometry, morphology, and current drive capabilities of Ir-based silicides

Abstract: A detailed study of the formation of iridium silicide obtained by ultrahigh vacuum annealing and atmospheric rapid thermal processing is proposed using x-ray photoelectron spectroscopy ͑XPS͒, transmission electron microscopy ͑TEM͒, and electrical characterizations. Using XPS analysis, the stoichiometry of each silicide phase ͑IrSi, IrSi 1.6 ͒ is identified. A model based on the variation of the measured intensity of the Ir 4f spectra is used to obtain the kinetic coefficients of reaction of Ir silicidation ͑E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The kinetic of formation of iridium silicides is controlled by diffusion of silicon species through the incipient layer of silicide. One of the latest analysis of iridium silicide formation on silicon shows that the interval of complete silicidation ranges between 450 8C and 530 8C [11]. It suggests that the transition temperature is higher on silicon carbide and iridium is a very promising Schottky barrier material for high temperature electronics.…”
Section: Introductionmentioning
confidence: 98%
“…The kinetic of formation of iridium silicides is controlled by diffusion of silicon species through the incipient layer of silicide. One of the latest analysis of iridium silicide formation on silicon shows that the interval of complete silicidation ranges between 450 8C and 530 8C [11]. It suggests that the transition temperature is higher on silicon carbide and iridium is a very promising Schottky barrier material for high temperature electronics.…”
Section: Introductionmentioning
confidence: 98%
“…Among the RE silicides, ytterbium silicide is a promising contact material, because it has a very low SBH on n-type silicon (0.2-0.4 eV) and is reported to have an epitaxial relation with Si(001) and (111). [7][8][9][10][11][12][13][14][15][16][17][18] Zhu et al reported that Yb silicide has a SBH of 0.27 eV with n-type Si by estimation of the SBH of the Yb silicide=p-Si contact. 19) There are several issues with this material as a contact material, including its high vulnerability against oxidation.…”
Section: Introductionmentioning
confidence: 99%